2019
DOI: 10.4103/jomfp.jomfp_133_19
|View full text |Cite
|
Sign up to set email alerts
|

Salivary calcium as a diagnostic tool for screening of osteoporosis in postmenopausal women

Abstract: Background: Women's health undergoes physiological, pathological and psychological changes after menopause. Reduced estrogen levels have been implicated in the pathogenesis of osteoporosis in postmenopausal women. Estrogen is also known to affect the salivary gland functions. To understand the association between serum estrogen, osteoporosis and salivary calcium, the present cross-sectional study was undertaken. Aim: The aim of this study is to determine salivary calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Two studies found that post-menopausal women with a lower BMD had higher salivary calcium than post-menopausal women without bone mineral changes [88] or pre-menopausal or pregnant women [45]. Long-term supplementation of vitamin D combined with calcium, did not significantly affect salivary calcium in osteoporotic women [40].…”
Section: Calciummentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies found that post-menopausal women with a lower BMD had higher salivary calcium than post-menopausal women without bone mineral changes [88] or pre-menopausal or pregnant women [45]. Long-term supplementation of vitamin D combined with calcium, did not significantly affect salivary calcium in osteoporotic women [40].…”
Section: Calciummentioning
confidence: 98%
“…The quality of case-control studies varied, ranging from one to eight and a 4.28 average out of nine (poor quality). This average is reflected by only 10 studies having a consecutive or representative set of cases [29,30,[38][39][40][41][42][43][44][45]. The quality of cross-sectional studies ranged between two and five, with a 3.86 average out of nine (unsatisfactory).…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Применение этого метода в клинической практике показало его высокую диагностическую информативность при различных заболеваниях [13,14,16]. Целесообразность использования данной биологической среды в качестве объекта исследования объясняется ее значимой физиологической ролью в организме, а также доступностью получения диагностического материала [17,18,19].…”
unclassified
“…Представленные данные подтверждают мнение специалистов о перспективности использования ротовой жидкости, как наиболее доступной и информативной биологической среды организма человека для проведения как диагностических, так и прогностических тестов у лиц как с соматической патологией [14,17,18], так и с воспалительными заболеваниями челюстно-лицевой области [13]. Кроме того, результаты исследования убеждают в актуальности широко обсуждаемого в специальной научной литературе последних лет вопроса о возможности осуществления динамического наблюдения за течением заболевания в процессе проведения лечения на основании оценки характера микрокристаллизации биологических жидкостей организма [14,16,27].…”
unclassified